Performance of a subject composition in engineering of oil painting. Stages of work above the diploma (Pedagogy of Higher and Secondary Education, 2009)
in clause the problem of creation of conditions of the system approach is considered at creation of a subject composition and development of creative abilities of the students in a context of work above the degree task.